Expressions of TWIST1 and CD105 markers in colorectal cancer patients and their association with metastatic potential and prognosis - Fahimeh Fattahi; Leili Saeednejad Zanjani; Somayeh Vafaei; Zohreh Habibi Shams; Jafar Kiani; Marzieh Naseri; Elmira Gheytanchi; Zahra Madjd (BMC, 2021)
Abstract Background TWIST1 and CD105, which contribute to tumor malignancy, are overexpressed in cancers. Accordingly, TWIST1 enhances epithelial-to-mesenchymal transition (EMT) and promotes the formation of cancer stem cells (CSCs). Also, CD105 is a neoangiogenesis marker in endothelial cells, which is introduced as a CSC marker in tumoral epithelial cells in several types of cancers. The present study was aimed to investigate expressions of TWIST1 and CD105 in colorectal cancer (CRC) patients. Methods Expressions of TWIST1 and CD105 in 250 CRC tissue samples were evaluated using immunohistochemistry on tissue microarrays (TMAs). In this regard, TWIST1 expression was investigated in the subcellular locations (cytoplasm and nucleus), while CD105 was mapped in endothelial cells and cytoplasmic tumor cells of CRC tissues. The association between the expression of these markers and clinicopathological parameters, as well as survival outcomes were analyzed. Results Results indicate a statistically significant association between higher nuclear expression levels of TWIST1 and distant metastases in CRC (P = 0.040) patients. In addition, it was shown that the increased nuclear expression of TWIST1 had a poor prognostic value for disease-specific survival (DSS) and progression-free survival (PFS) (P = 0.042, P = 0.043, respectively) in patients with CRC. Moreover, analysis of CD105 expression level has revealed that there is a statistically significant association between the increased expression of CD105 in tumoral epithelial cells and more advanced TNM stage (P = 0.050). Conclusions Our results demonstrate that nuclear TWIST1 and cytoplasmic CD105 expressions in tumor cells had associations with more aggressive tumor behavior and more advanced diseases in CRC cases.